Integrated cross-realm planning: A decision-makers' perspective. (November 2015) - Álvarez-Romero, Jorge G.; Adams, Vanessa M.; Pressey, Robert L.; Douglas, Michael; Dale, Allan P.; Augé, Amélie A.; Ball, Derek; Childs, John; Digby, Michael; Dobbs, Rebecca; Gobius, Niilo; Hinchley, David; et al.
Abstract: Pursuing development and conservation goals often requires thinking and planning across terrestrial, freshwater and marine realms because many threats and social–ecological processes transcend realm boundaries. Consequently, effective conservation planning must consider the social and ecological links between realms and follow a cross-realm approach to allocate land/water uses and conservation actions to mitigate cross-realm threats and maintain cross-realm ecological processes. Cross-realm planning requires integrating multiple objectives for conservation and development, and assessing the potential co-benefits and trade-offs between them under alternative development scenarios. Despite progress in cross-realm planning theory, few fully-integrated and applied cross-realm plans exist. The gaps between research and implementation are not unique to cross-realm planning, but are accentuated by the complexity of spatial decision-making entailed. Based on a collaborative process including scientists, resource managers and policy-makers, we developed an operational framework for cross-realm planning based on up-to-date thinking in conservation science, but offering practical guidance to operationalise real-world planning. Our approach has a strong theoretical basis while addressing the visions and needs of decision-makers. We discuss the foundations and limitations of current approaches in cross-realm planning, describe key requirements to undertake this approach, and present a real-world application of our framework. Highlights: Few applied integrated cross-realm planning exist due to planning complexities. Our framework can help to operationalise real-world cross-realm planning. Key goals are mitigating cross-realm threats and maintaining cross-realm processes. Assessing co-benefits and trade-offs between multiple objectives is fundamental. Scenario analyses are useful tools given limited data on cross-realm processes. We present a case study that demonstrates these aspects of our framework.